Variasi Morfometri Papilio polytes L. (Lepidoptera: Papilionidae) di Beberapa Lokasi di Sumatera Barat - Rury Makhzuni; - Syaifullah; - Dahelmi (Universitas Andalas, 2013)
The research on morphometry variation of Papilio polytes L. (Lepidoptera: Papilionidae) was conducted on December 2011 until April 2012 in West Sumatera (Padang Panjang, Padang and Marak Island). Papilio polytes were directly collected from the field and morphological measurement was conducted in Genetic Laboratory, Biology Department, Andalas University Padang. The morphological characters were significantly different among males. Those characters were forewings length, hindwings length, antenna length, eyes distance, foreleg length and wing venations. While differentiation also found among females. Those characters were forewings length, hindwings width, foreleg length and wing venations. There was a high of female morphological differentiation between Padang - Marak island and Padang Panjang – Marak Island. Male individual had low variation between that places.Keywords: variation, morphometry, Papilio polytes, West Sumatra